The effects of a 3D based video intervention on visual-perceptual-motor skills in silat athletes - Chok, Esther Wai Kuin (2019)
This study aimed to assess the visual-perceptual-motor-skills (VPMS) of elite Silat athletes when responding to attacks of varying onset times. VPMS – the ability to perceive affordances in the environment and respond appropriately – may be inferred from visual search behavior (VSB) and reaction time (RT). 1 seasoned male elite Silat athletes and 1 junior male elite Silat athlete were recruited for the study. Participants responded to a attacks of different onset times from a virtual opponent projected on a three-dimensional (3D) stereoscopic screen. Responses and RT to each attack was recorded on 3D motion analysis cameras. VSB, comprising the number of fixations, duration of fixations (FD) and quiet eye (QE) duration, was recorded using a mobile eye tracker. Fixations were categorized into 11 locations on the body (Lee et al., 2013). With a decrease in attack onset time, it was hypothesized (i) pertaining to VSB of elite Silat athletes, the total number of fixations will increase, duration of fixations will decrease, duration of quiet eye will decrease, and (ii) the reaction time (RT) of elite Silat athletes will increase. RT increased while FD decreased with quicker onset of attacks. This study provides insight into the visual search strategy adopted by elite Silat athletes in various situations and may serve as a basis for future training recommendations.